2010
DOI: 10.1002/path.2785
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic roles of TGF‐β in cancer

Abstract: The transforming growth factor-β (TGF-β) signalling pathway plays a critical and dual role in the progression of human cancer. During the early phase of tumour progression, TGF-β acts as a tumour suppressor, exemplified by deletions or mutations in the core components of the TGF-β signalling pathway. On the contrary, TGF-β also promotes processes that support tumour progression such as tumour cell invasion, dissemination, and immune evasion. Consequently, the functional outcome of the TGF-β response is strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
346
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(357 citation statements)
references
References 176 publications
(195 reference statements)
5
346
0
6
Order By: Relevance
“…It is important to remember that other genes also exhibit different roles in normal and neoplastic tissues. It is worth mentioning that TGFb acts as a tumor suppressor in normal tissue, but plays an oncogenic role in tumors, 32 by promoting cell growth and development of epithelial-to-mesenchymal transition. 33,34 Interestingly, in our study, we identified two different patterns of FGFR2 immunostaining: cytoplasmic and nuclear.…”
Section: Fgfr2 Mutationsmentioning
confidence: 99%
“…It is important to remember that other genes also exhibit different roles in normal and neoplastic tissues. It is worth mentioning that TGFb acts as a tumor suppressor in normal tissue, but plays an oncogenic role in tumors, 32 by promoting cell growth and development of epithelial-to-mesenchymal transition. 33,34 Interestingly, in our study, we identified two different patterns of FGFR2 immunostaining: cytoplasmic and nuclear.…”
Section: Fgfr2 Mutationsmentioning
confidence: 99%
“…During the first stages of the development of primitive tumors from epithelial origin, the TGFb/Smad cascade acts as a tumor suppressor mainly through inhibition of cell proliferation and/or promotion of cell apoptosis (11,12,17). Contrarily, during the later stages, the TGFb cascade promotes tumor progression mainly by its ability to stimulate epithelial-to-mesenchymal transition, tumor invasion, metastatic dissemination, and/or evasion of the immune system (12,13,17). With regard to bone cancers, most studies have focused on the role of TGFb in the development of bone metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In normal and premalignant cells, TGF-b enforces homoeostasis and suppresses tumour progression directly through cell autonomous regulation of apoptosis and growth arrest or indirectly through blockage of paracrine factor production in the tumour stroma. However, when cancer cells lose the TGF-b tumour suppressive responses, they can utilize TGF-b as a potent promoter of cell motility, invasion, metastasis and tumour stem cell maintenance 1,10 .…”
mentioning
confidence: 99%